Penegakan Hukum Pidana terhadap Tindak Pidana Makar di Aceh dalam Perspektif Hak Asasi Manusia - Wicaksono, Adito; Laela, Sofa (Decisio: Jurnal Ilmiah Hukum, 2024)
The enforcement of criminal law against treason in Aceh remains a complex issue due to its legal, social, cultural, and political dimensions. The broad interpretation of treason under Indonesia's Penal Code, particularly Articles 87, 104, 106, 107, and 110, often leads to concerns about human rights violations, particularly in the context of freedom of expression. This study examines the implementation of treason laws in Aceh and its compatibility with human rights principles. The research highlights the challenges faced by law enforcement in maintaining national security while ensuring the protection of civil liberties. A qualitative normative legal research method was used, analyzing primary legal sources such as legislation and court rulings, complemented by secondary sources like legal literature and previous studies. Data collection was conducted through an extensive literature review with qualitative descriptive analysis applied to interpret the findings. The results indicate that the enforcement of treason laws in Aceh is often inconsistent and lacks sensitivity to the region’s historical and cultural context. A strict and repressive approach has led to public distrust in law enforcement and hindered reconciliation efforts. The study underscores the need for legal reforms, including clearer definitions of treason and improved judicial transparency. It also recommends a more inclusive, human-rights-based approach in law enforcement to maintain national stability while respecting fundamental freedoms.